Time-Series Growth in the Female Labor Force - Smith, James P.; Ward, Michael P. (Journal of Labor Economics, 1985)
In this paper we investigate the reasons for the growth in the female labor force in America during the twentieth century. In our research, we study the longer-term trends since 1900 and conduct a more intensive examination of developments after the Second World War. On the basis of our work, we conclude that rising real wages accounted for 60% of the total growth in the female labor force. Half of this wage effect in expanding labor supply was the fertility-reducing consequence of a higher female wage.